Educational leadership and sustainable learner academic performance at schools in the Lejweleputswa education district - Mokgobo, Mosweu Sam (Welkom: Central University of Technology, Free State, 2015)
The study sought how educational leadership can assist in sustaining learner academic performance (LAP) in schools in the Lejweleputswa education district. Some secondary schools in the district have developed a tendency of being perennial underperformers. At the time of the study there were schools that never performed above 80% for at least ten years. These schools rely heavily on external support for them to be able to perform, learners from such schools being taught by teachers from other schools. Every year these schools fail to perform to the expected level despite being supported and assisted by the department through camps and other intervention measures. To combat this situation, a large amount of money is spent to enhance LAP in general and in particular that of Grade 12 learners, since the Grade 12 results are still the measuring tool to measure performance (Lejweleputswa District: 2012). The pool of applicable and relevant qualified teachers in key subjects, force education districts to be involved in a large number of interventions to uphold and better the performance of learners in general and for Grade 12 in particular to adhere to the goals set by the Action Plan 2014 (DBE, 2012a). The key problem resounds about secondary schools that are unable to sustain or improve LAP when financial support for intervention strategies rolled out from the district offices, is no longer sustainable. The literature pursued in this study covers leadership in general, educational leadership and various aspects of educational leadership. Important to consider is that instructional leadership, transformational leadership, collaborative leadership, as well as sustainable leadership from both schools and district education offices have a role to play to ensure learner academic performance. The climate within a school and its importance regarding academic performance is another aspect addressed in this study. The methodology of the study followed a concurrent triangulation approach where quantitative and qualitative data collection and analysis took place simultaneously. The quantitative analysis employed descriptive statistics where the sample was described in terms of educator levels; gender; qualification levels and teaching experience. Various aspects, inclusive of how vertical (upward and downward) educational leadership (EL) are experienced by all educator levels; overall school climate perceived by all educator levels; empowerment to promote effective teaching and learning by all educator levels; present feelings about teaching as a career; and ultimately consideration in term of leaving the teaching profession by all educator levels. The open-ended questionnaire sought to explain the views and opinions of educators on all levels from a qualitative standpoint relating to the acknowledgement of the existence of the relationship between EL and LAP; and the consequences of academic intervention strategies and their successes for LAP in the Lejweleputswa education district. This study attempted to outline the rationale for improving EL for the successful enhancement of LAP in the Lejweleputswa Education district. The study provided an aggressive approach and action plan towards equipping EL to a level of functionality which will be implemented over the next two years in the Lejweleputswa district where targets will be managed at all levels in the leadership hierarchy.
Thesis
Keywords: Educational leadership - South Africa - Lejweleputswa District; Academic achievement; Education, Secondary - South Africa - Lejweleputswa District; School management and organization